2019
DOI: 10.1155/2019/9328621
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Dermatophytosis and Antifungal Activity of Ethanolic Crude Leaf Extract ofTetradenia ripariaagainst Dermatophytes Isolated from Patients Attending Kampala International University Teaching Hospital, Uganda

Abstract: Dermatophyte infections are a global health problem but neglected in Uganda. This work aimed at determining prevalence of dermatophytosis and antifungal activity of ethanolic crude leaf extract of Tetradenia riparia against dermatophytes isolated from patients attending Kampala International University Teaching Hospital (KIU-TH), Uganda. A total of 100 samples of skin and nail scrapings were collected and processed using standard microscopy (KOH) and cultural methods. T. riparia leaves were collected and proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 29 publications
2
18
0
Order By: Relevance
“…In this study, tinea corporis is the third common manifestation in prevalence and accounted for 13.9% of all tineas. Similar results were found in Ethiopia 21,22 and in Egypt, 36 India 30,37, and Brazil. 38,39 Whereas, Singh et al, 30 Naseri et al, 25 and Bhatia et al, 40 found tinea corporis as the dominant form of dermatomycosis ranging from 33.1%-39.5%.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…In this study, tinea corporis is the third common manifestation in prevalence and accounted for 13.9% of all tineas. Similar results were found in Ethiopia 21,22 and in Egypt, 36 India 30,37, and Brazil. 38,39 Whereas, Singh et al, 30 Naseri et al, 25 and Bhatia et al, 40 found tinea corporis as the dominant form of dermatomycosis ranging from 33.1%-39.5%.…”
supporting
confidence: 85%
“…Dermatomycosis was higher among females than males except for fingernail infection. Adult' age group (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44) was more affected by dermatomycosis than the other age groups. The high prevalence of tinea corporis occurred in males rather than in females.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatophytes grow best in warm and humid environments; hence, they are more common in tropical and subtropical regions (Havlickova et al 2008). Therefore, dermatophytoses are more prevalent in Libya, Iran, Iraq, Turkey, Ethiopia, Uganda, Italy and other warm countries than in countries with colder climates (Ozkutuk et al 2007;Bitew 2018;Kakande et al 2019). The geographical region is also an indicator of the distribution of individual species of dermatophytes.…”
Section: Problems In Diagnosis and Treatment Of Dermatophytosesmentioning
confidence: 99%
“…It is worth noting that zoophilic dermatophytes isolated from animals are responsible for symptomatic infections, but they are also often asymptomatic, making an animal a carrier (Gnat et al 2018b). In this case, they may become a source of epidemics (Kakande et al 2019). Additionally, when the transmission onto a human takes place, zoophilic and geophilic species cause acute mycoses with strongly expressed symptoms of inflammatory response (Baumgardner 2017;Fike et al 2018;Pereira et al 2018;Vanam et al 2019;Gnat et al 2019f).…”
Section: Problems In Diagnosis and Treatment Of Dermatophytosesmentioning
confidence: 99%
“…Dermatophytosis is a widespread disease with infection rates reaching 20–25% of the human population each year [ 1 3 ]. The major etiological agents of this disease are filamentous fungi called dermatophytes, which have high affinity to keratinized structures, e.g., skin, hair, and nails [ 1 , 4 6 ].…”
Section: Introductionmentioning
confidence: 99%